Pengaruh Kebisingan Lalu Lintas Terhadap Ketergangguan Pegawai Kantor Bkd Provinsi Sulawesi Tenggara - Basri, M; Lakawa, Irwan; sulaiman, Sulaiman (Universitas Sulawesi Tenggara, 2020)
Noise is unwanted sound, which can impair the health and comfort of the environment, have a source and propagates through a medium. Provincial Civil Service Agency of Southeast Sulawesi’s Office is located at the intersection of Drs. H. Abdullah Silondae Street, Laute Street and Malik Raya street with dense vehicle traffic, which Drs. H. Abdulah Silondae Street is the route of public transportation to the downtown to UHO Campus. The purpose of this research is to analyze the noise level due to the activities of the traffic in the area of Provincial Civil Service Agency of Southeast Sulawesi’s Office, analyzing the annoyance perception employees due to the traffic noise and the characteristics of respondents, and analyze the influence of noise level against the employees annoyance level. Data analysis of obtained that the average noise level in the area of Provincial Civil Service Agency of Southeast Sulawesi’s Office has passed the quality standards of noise to the office area. The perception of employees due to interference noise is 44% of the respondents who stated not bothered by noise in the area, 24% of respondents who stated a bit distracted, 24% stated quite disturbed, and 8% declared disturbed. As for the noise have significant influence towards employees level of annoyance.